Tara tannin a natural product with antifouling coating application - Bellotti, Natalia (2012)
The international trade by marine transportation has increased continuously since the 70s. The undesirable accumulation of a wide variety of marine organisms (biofouling) on ship hulls can lead to significant increased costs, principally by increased fuel consumption. On the other hand, there is a great concern about the biocides commonly used in commercial antifouling (AF) protective systems due to the high concentration encountered in coastal areas and the potential damage they could cause to marine organisms. As a consequence, the development of alternative AF coatings with new natural products as biocides inhibit is a key factor. In this approach, tara tannin (TT) is being proposed as a promising solution. It is important to note that TT is obtained from the pods of the tree avoiding its cutting down. The aim of this research was, primarily, to explore the possible application of a natural and abundant product, such as the TT, in the preparation of AF coatings. So, a TT derivative was obtained and characterized to be employed as the bioactive compound in AF coatings. Previous to the immersion in natural environments, the dissolution of TT from AF coating in artificial sea water (ASW) was studied. TT was incorporated into the coating as zinc "tannate". One of the tested coatings proved to be efficient in AF protection in natural sea water (NSW) at Mar del Plata (38°08′17″S-57°31′18″W) harbor during eight months. The addition of 2% by weight of zinc oxide to the coating extended its service life until the year.